Implementation of Experimental Design Techniques to Optimize Immunoglobulins Detection with Ultrasensitive Sandwich Immunoassays - Cecilia Scandurra; Paolo Bollella; Ronald Österbacka; Francesco Leonetti; Eleonora Macchia; Luisa Torsi (Advanced Sensor Research, 2022)
Abstract The ultrasensitive measurement of protein markers plays a pivotal role in the early diagnosis of infectious and progressive diseases. Recently, digital methods such as those enabled by the Simoa Planar Array technology (SP‐X System) have made significant progress in reaching ultrasensitive detection with clinically relevant protein biomarkers. The elicited Simoa technology is based on printing high‐density capturing antibodies layers on the bottom of the wells of a microtiter plate, followed by a standard sandwich‐type immunometric chemiluminescent detection. Such assay, reaching limit‐of‐detections (LODs) in the low femtomolar range, can be conveniently customized. An optimized Simoa SP‐X assay for detecting and quantifying immunoglobulin M (IgM, non‐specific indicator of inflammation) is developed herein and optimized. A full factorial experimental design is undertaken to optimize the assay, leading to a reduced experimental effort and increased quality of the information obtained concerning the traditional one‐variable‐at‐a‐time approach. The optimization process leads to an IgM LOD of 4 fm that compares well with those achieved with commercially available Simoa Planar Array kits. Remarkably, depositing both the capturing and detecting layer from a solution (0.1 µg mL−1) one order of magnitude less concentrated than in standard kits is needed, and the assay's cost is sizably reduced.